ANALISIS PRODUKSI DAN EFISIENSI BERAS - Dede Ruslan (Quantitative Economics Journal, 2014)
The purpose of this study to find out if the factors of production could give contribution tu the production or income and the cost of rice production, theeconomy efficiensy of rice production. It is hoped thet the result of this study could give information to farmers and local government in Deli Serdang about the contributions of the factors of production to the production or income and the cost of rice farm opration production. From the study, it is shown that the characteristic of model of production, the using of the factors of production and teh cost of production opportunity is increasing returns to scale or decreasing cost industries. The economy scale of rice production describes that the estimate cost of corn farm production. The analysis of economy efficiensy from the rice production was taken form condition that the produtions marginal cost is lowerthan the corn scale. From the contributions of field, seed, fertilizer and labortoward the rice production, it can be explained that rice production can be raisedby increasing the field, seed, fertilizer, and labor usings.